Mobilidade sustentável e densidade urbana na Grande Vitória-ES : análise com base nos resultados da pesquisa de origem e destino de 2007 - Borges, Eduardo Schwartz (2018)
Since the second half of the twentieth century, the concern about the sustainable development and the growth of urban problems in various parts of the world have raised the need to develop specific studies in new areas of knowledge, such as urban sustaina